Blindness and Design: Kneass’ Philadelphia Magazine for the Blind (1899) - Vanessa Warne (Cahiers Victoriens et Edouardiens)
This article focuses on the representation of women poets in a significant poetry anthology of the Edwardian era, William Archer’s Poets of the Younger Generation, published by John Lane in 1902. In Poets, Archer attempts to canonize thirty-three poets of the late nineteenth century, including nine women poets (among them Katharine Tynan Hinkson, Nora Hopper, Alice Meynell, and Rosamund Marriott Watson). Archer’s entries are accompanied by woodcut illustrations by Robert Bryden, based on photographic portraits of the poets. This essay situates these woodcuts within the context of late-Victorian celebrity, the aesthetic revival in woodcut and wood-engraved illustration, and the increasing presence of the authorial portrait in the age of mechanical reproduction. My essay then analyses the complex interaction between the critical vocabulary Archer uses and Bryden’s images. As Archer’s critical commentary gradually builds a vocabulary of judgment and hierarchy based on assumptions regarding national and gender identity, Bryden’s images reinforce this by framing women poets as ‘poetesses’, enclosed within decorative borders.